The Impact of Financial Incentive on the Performance of Urban Health Centers in Iran - S Rouhani; M James; R Beech (Tehran University of Medical Sciences, 2005)
In the last decade, main health financing reforms in Iran's integrated health care delivery system, have provided some degree of financial incentive both to the providers of secondary and tertiary care in supply side, and the consumers of these services in demand side, leaving the primary health facilities at lower level of system with fixed financing method in macro and micro levels. But in recent years, alternative set of primary health care delivery has been introduced to primary health care delivery system in Iran that provides financial incentive to the provider of services in new initiative, both at micro and macro levels. Regardless of the impact of financial incentive on the performance of secondary and tertiary facilities, we compared the performance of different primary health care providers each with different method of financing. In this comparative study, secondary and primary data were gathered cross-sectionally. In this article, the impact of financial incentive on the financial performance of alternative sets of primary health centers in a region of Iran will be reported.